IDENTIFIKASI SELF ESTEEM PADA ANAK KORBAN PERCERAIAN ORANG TUA DI SMP NEGERI 9 KOTA JAMBI - Nur Aliza; Muhammad Ferdiansyah; Muhammad Alridho Lubis (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
The presence of a parent figure in a child's mental growth is very important. Dysfunctional family relationships due to the breakup of husband-wife relationships can cause a family atmosphere that is divided by poor family interactions and can affect child development. One aspect that is important to consider and can affect children is self esteem. This study aims to identify the condition of children's self esteem who have divorced parents in the aspects of self-esteem, feelings of ability and feelings of acceptance by the surrounding environment. This research is a type of qualitative research that uses descriptive analytical methods and focuses on 8th grade students of SMP Negeri 9 Jambi City who experience family and self problems based on the results of the General AUM and Learner Needs Questionnaire. The informants of this study amounted to 10 children using purposive sampling technique which is a sampling method from specific criteria in determining informants. Through the results of the study, it was found that children who were victims of divorce at SMP Negeri 9 Jambi City had very good feelings of worth and feelings of self-respect. Children are able to recognize themselves and make principles that are applied in everyday life as a form of self-esteem. Although the conditions they experience at this adolescent age are quite heavy, they have dreams and goals that they believe they can achieve. This is also supported by the acceptance of themselves by their friends and extended family.Most children are very reconciled with all the circumstances that befall them. Some of the children also felt unaccepted by their environment. However, the children still had good self-esteem and confidence.